Relationship between self-reported health and neuroticism in older adults: a scoping review - Meire Cachioni; Gabriela Cabett Cipolli; Vanessa Alonso; Ruth Caldeira de Melo; Patrick Alexander Wachholz; Constança Paúl (Brazilian Society of Geriatrics and Gerontology, 2023)
This scoping review aims to identify and map the existing literature regarding the relationship between neuroticism and self-reported health in community-dwelling older adults. We adopted the Joanna Briggs Institute Manual for Evidence Synthesis recommendations and followed the PRISMA-SCr when reporting it. The search was performed on ten different databases, including: Cumulative Index to Nursing and Allied Health Literature, Cochrane, Embase, PsycArticles, PsycInfo, United States National Library of Medicine, Scopus, Web of Science, Ageline and Biblioteca Virtual em Saúde/Centro Latino-Americano e do Caribe de Informação em Ciências da Saúde databases until February 2021. Data screening and extraction were performed by two independent reviewers. We included primary studies with older adults (≥60 years) [participants] that adopted validated instruments to assess neuroticism and self-reported health [concept] in the community [context], published in Portuguese, English, or Spanish. We identified 3453 articles and included 15 studies in this review. We extracted the main categories of included studies, characteristics of the participants, methodological issues, and biopsychosocial factors. Outcomes were reported in three sections: Focus of studies; Definitions and measures of neuroticism and self-reported health; Associations with biopsychosocial factors. We found an association between high neuroticism and poor self-reported health. Some biopsychosocial factors may influence this relationship, such as chronic diseases, depression, social support, and a sense of control, which must be considered in future studies to shed light on this topic.